The potential impact of the fiscal transfers under the EU cohesion policy programme - Veld, Jan in't 1962-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
The European Union uses large-scale fiscal transfers to national and regional levels to foster economic and social cohesion. This paper gives an ex-ante model-based analysis of the potential macro-economic impact of these fiscal transfers between member states as planned under the Cohesion Policy programme 2007-2013. The simulations show the costs and benefits of Structural Funds spending on beneficiary and donor countries in the EU. The increase in public investment has positive externalities and yields significant output gains in the long run due to sizeable productivity improvements. In the short run it can lead to crowding out of private spending.
Economic Papers